THE IMPORTANCE OF ENTREPRENEURSHIP, OPPORTUNITY, AND GOVERNANCE FOR LATIN AMERICA: PROSPERITY INDEX TRENDS BETWEEN 2009 AND 2014 - Alfaiate, Joana (European Scientific Journal, ESJ, 2015)
The Latin American and Caribbean region has witnessed noticeable economic growth over the last decade. How some countries in the region have resisted the financial crisis by continuing to grow has also not gone unnoticed by the international community. Whether said development and growth can keep its pace or not, however, remains the big question. This paper addresses this issue using a multidimensional approach that provides a broader picture of the current situation in Latin America. Using the rich data included in the Legatum Prosperity Index, an index that measures prosperity as a combination of wealth and wellbeing across 142 countries, this paper analyses how entrepreneurship, opportunity, and good governance are key elements to promote prosperity. In particular, this paper discusses how the enhancement of entrepreneurial activities, backed up by improvement in technological infrastructure, can only produce lasting, positive results in Latin America if inequality of opportunity is reduced, and good governance – an area showing acute problems in the region – is promoted.